BRAVERY IN EKA KURNIAWAN’S NOVEL BEAUTY IS A WOUND - Yodi Kurniawan; Zulfan Sahri (JOURNAL OF LANGUAGE, 2021)
In  Beauty Is A Wound, Kurniawan portrays three kinds of bravery:  physical bravery, social bravery, and moral bravery. These three kinds of bravery are constructed through the roles of the protagonist during the Japanese invasion in Indonesia. The protagonist uses her physical bravery to fight back against anybody who wants to hurt her or the people she loves. The second is social bravery; the protagonist has courage to have dispute with the person who wants to take advantages and threaten her; her action disfigures her image in front of many people. In her moral bravery, the protagonist does not expect any respect from anyone; even for a debt payment and she finally must do a disgusting work to find out her grandmother’s treasure she buries in a septic tank pipe. The method used to do the analysis is descriptive research method due to its suitability for describing the data properly. The result indicates that the protagonist acts bravely to defend her and her friends’ rights despite living as a prisoner; she is willing to prostitute herself for her and her friends’ safety; she then morally struggles to pay all her debt. Three kinds of bravery are found in the novel.